1995
DOI: 10.2172/72981
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance behavior of UNiGe

Abstract: Los Alamos National Laboratory, an affirmative action/equal opportunity employer, is operated by the University of California for the U.S. Department of Energy under contract W-7405-ENG-36. By acceptance of this article, the publisher recognizes that the US. Government retains a nonexclusive, royalty-free license to publish or reproduce the published form of this contribution, or to allow others to do so, for US. Government purposes. The Los Alamos National Laboratory requests that the publisher identify this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The 2ϫ2ϫ1.6 mm 3 single crystal of UNiGe, grown by a modified Czochralski tri-arc technique, is the same as the one used in previous neutron measurements 7 and in the determination of the BϪT magnetic phase diagram. [12][13][14] The sample was sealed under a He atmosphere in a vanadium can which was mounted on the cold finger of a Displex closedcycle refrigerator which in turn was mounted on the single crystal diffractometer ͑SCD͒ at LANSCE, the spallation neutron source at Los Alamos National Laboratory. A white beam of pulsed neutrons is scattered by the sample onto an area detector (25ϫ25 cm 2 ; position-sensitive; 3 He gas-filled counter͒ and the wavelengths ͑0.5 -5 Å͒ are determined by their time of flight from the source to the detector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2ϫ2ϫ1.6 mm 3 single crystal of UNiGe, grown by a modified Czochralski tri-arc technique, is the same as the one used in previous neutron measurements 7 and in the determination of the BϪT magnetic phase diagram. [12][13][14] The sample was sealed under a He atmosphere in a vanadium can which was mounted on the cold finger of a Displex closedcycle refrigerator which in turn was mounted on the single crystal diffractometer ͑SCD͒ at LANSCE, the spallation neutron source at Los Alamos National Laboratory. A white beam of pulsed neutrons is scattered by the sample onto an area detector (25ϫ25 cm 2 ; position-sensitive; 3 He gas-filled counter͒ and the wavelengths ͑0.5 -5 Å͒ are determined by their time of flight from the source to the detector.…”
Section: Methodsmentioning
confidence: 99%
“…While the magnetization studies revealed two pronounced metamagnetic transitions for Bʈc, a far more complex magnetization behavior with up to four transitions for the b-axis was observed. de Boer's original data, 12 which were taken by sweeping the magnetic field at fixed temperatures, have since been supplemented by temperature scans 13,14 at fixed fields up to 20 T, and the resultant phase diagram is shown in Fig. 8.…”
Section: A Consideration For the B؊t Phase Diagramsmentioning
confidence: 99%